2017
DOI: 10.1080/21691401.2017.1324467
|View full text |Cite
|
Sign up to set email alerts
|

miR-133 involves in lung adenocarcinoma cell metastasis by targeting FLOT2

Abstract: Our study revealed the mechanism that miR-133 suppresses lung adenocarcinoma metastasis by targeting FLOT2 via Akt signalling pathway, implicating a potential prognostic biomarker and therapeutic target for lung adenocarcinoma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Results of prediction from bioinformatics website confirmed that FLOT2 was in targeting relationship with miR‐351. Similarly, a former paper implicated that in the invasion and migration of lung adenocarcinoma, miR‐133 targeted with FLOT2 . Flotillins, also named as reggie proteins, consist of FLOT1 and FLOT2, two commonly expressed and highly conserved proteins .…”
Section: Discussionmentioning
confidence: 89%
“…Results of prediction from bioinformatics website confirmed that FLOT2 was in targeting relationship with miR‐351. Similarly, a former paper implicated that in the invasion and migration of lung adenocarcinoma, miR‐133 targeted with FLOT2 . Flotillins, also named as reggie proteins, consist of FLOT1 and FLOT2, two commonly expressed and highly conserved proteins .…”
Section: Discussionmentioning
confidence: 89%
“…Knockdown of Flot-2 inhibits the growth and invasion of human esophageal squamous cell carcinoma [32]. Targeting FLOT2 via the Akt signaling pathway, miR-133 and miR-485 inhibits lung metastasis [33,34]. miR-34a inhibits melanoma cell proliferation and metastasis by directly targeting the FLOT2 gene [35].…”
Section: Discussionmentioning
confidence: 99%
“…The Flotillin family contains two homologous isoforms, flotillin1 (FLOT1) and 2 (FLOT2), which play essential physical roles in various cellular processes such as adhesion, reorganization of the actin cytoskeleton, endocytosis, phagocytosis, and transduction of cellular signals. Flotillin-1 oligomerizes to build microdomain scaffolds that are involved in molecular sorting [21][22][23], cytoskeletal dynamics [24], clathrinindependent endocytic pathways [25][26][27] and phagosome trafficking [14][15][16][17][18]. However, it also promotes cell proliferation [22] and T cell activation [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Butz H et al proved that validated CAV1 and FLOT1 as miR-124-3p targets [26]. Huang et al showed that FLOT2 identified as a direct target of miR-133 in human lung adenocarcinoma [27]. And Wang et al identified Flot2 as a direct target of miR-802 in PCa cells [28].…”
Section: Introductionmentioning
confidence: 99%